Genetic and ecological effects of chronic forest fragmentation on a critically endangered tree species - Karina Aparecida Soares de Pádua (2023)
Anthropogenic disturbances, such as deforestation and agricultural expansion, have led to habitat fragmentation and degradation, negatively impacting the species that inhabit these forest remnants. In this study, we investigated the effects of forest fragmentation on Dinizia jueirana-facao, a rare species endemic to the Atlantic Forest and critically endangered. Based on theories that point to reduced gene flow due to forest fragmentation, resulting in negative effects on genetic diversity and ecological processes, we hypothesized that these effects are present in D. jueirana-facao, considering the occurrence of reduced population sizes and seed dispersal by barochory. We also tested whether the demographic structure of the remaining localities of D. jueirana-facao fit the reverse J-shaped distribution model. Using informative sets of SNPs derived from double-digest restriction site-associated DNA sequencing (ddRADseq), we investigated dispersal distances, connectivity between fragments, genetic diversity and quantified historical and contemporary gene flow. Our results indicated that pollen dispersal occurs at short distances, with most outcrossed pollination events occurring within populations. In addition, we observed a reduction in contemporary gene flow compared to historical, indicating temporal changes in gene flow related to recent forest fragmentation. Our results also indicated an absence of inbreeding, no apparent loss of genetic diversity and a healthy demographic structure. Although these results already have important implications for the conservation and management of D. jueirana-facao, we emphasize that a more comprehensive understanding of ecological and evolutionary dynamics is still needed, given the current scenario of habitat loss, degradation and fragmentation.